Polarization miniature LED device capable of adjusting light emitting color and preparation method thereof

By introducing bait ions into the double perovskite system and mixing them with inorganic polysilazane solution, polarized LED devices with adjustable luminescent color were prepared, solving the challenges of epitaxial growth control and wavelength adjustment of polarized laser and nano/micrometer materials in the prior art, and achieving high stability and high polarization micro-nano light sources.

CN119816161AActive Publication Date: 2025-04-11SHANDONG UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411790331.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The prior art has challenges in achieving epitaxial growth control and precise wavelength adjustment of polarized lasers and nano/micromaterials, especially when used in micro/nanode devices.

Method used

By introducing bait ions into the double perovskite system, the doping concentration is used to control the luminous color by using energy transfer, and mixing the quantum dot solution with the inorganic polysilazane solution, controlling the formation of silicon oxide and spin coating into a film, a polarized LED device with adjustable luminous color is prepared.

Benefits of technology

A polarized LED device with adjustable luminescent color is realized, providing new ideas for application in micro/nano devices, and improving the stability and polarization of optical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816161A_ABST
    Figure CN119816161A_ABST
Patent Text Reader

Abstract

The invention discloses a polarized LED device capable of adjusting light emitting color and a preparation method thereof, and the preparation method comprises the following steps: mixing cesium oleate, erbium oleate, indium acetate, bismuth acetate, silver acetate, benzoyl chloride, dioctyl ether, oleic acid and oleylamine according to a ratio, heating to 120-170 DEG C in a nitrogen atmosphere, reacting for 1-5 minutes, and stopping the reaction; adding a mixed solution of cyclohexane and ethyl acetate into the reaction solution, centrifuging, collecting precipitates, repeating the operation to obtain quantum dots, and dispersing the quantum dots in cyclohexane to obtain a quantum dot solution; the preparation method comprises the following steps: mixing a quantum dot solution with an inorganic polysilazane solution, performing ultrasonic dispersion, heating the mixed solution to 70-90 DEG C, and performing stirring reaction for 10-15 hours to hydrolyze inorganic polysilane to generate a compact silicon oxide shell so as to obtain slurry; and preparing the slurry into a film, and attaching the film to an LED device. Erbium ions are introduced into a double perovskite system, and energy transfer is utilized to realize doping concentration control of luminescence color.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite quantum dot material modification, and in particular relates to a polarized LED device capable of adjusting luminous color and a preparation method thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Linearly polarized luminescence is a special luminescence phenomenon, and its oscillation direction is in one plane. Compared with randomly polarized light, linearly polarized light has higher light intensity, stronger penetration ability and better directionality, so it has a wide range of applications in optical communications, laser technology, biomedical imaging and other fields. Methods for realizing polarized lasers include introducing polarization-selective elements in the resonator, such as Brewster plates, axons, or using uniaxial crystals and special processing directions. These processes are relatively complex and not suitable for micro / nano devices. In recent years, with the development of micro-nano technology, the development of polarized micro-nano light sources has gradually become a research hotspot. However, this field also faces many challenges. Among them, the epitaxial growth control of nano / micro materials and the precise adjustment of wavelength are two major technical difficulties. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a polarized LED device with adjustable luminous color and a preparation method thereof, wherein bait ions are introduced into the double perovskite system, and energy transfer is used to realize doping concentration control of the luminous color. At the same time, a quantum dot solution is mixed with an inorganic polysilazane solution, silicon oxide generation is controlled and spin-coated into a film, and a polarized micro-nano light source is prepared for use in the device.

[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a polarized LED device with adjustable emission color, comprising the following steps:

[0007] Cesium oleate, erbium oleate, indium acetate, bismuth acetate, silver acetate, benzoyl chloride, dioctyl ether, oleic acid and oleylamine were mixed in proportion, heated to 120-170° C. in a nitrogen atmosphere, reacted for 1-5 minutes, and then the reaction was stopped;

[0008] Adding a mixture of cyclohexane and ethyl acetate to the reaction solution, centrifuging, collecting the precipitate, repeating the operation to obtain quantum dots, dispersing the quantum dots in cyclohexane to obtain a quantum dot solution;

[0009] The quantum dot solution and the inorganic polysilazane solution are mixed and dispersed by ultrasonication, and then the mixed solution is heated to 70-90° C. and stirred for reaction for 10-15 hours to hydrolyze the inorganic polysilane to form a dense silicon oxide shell to obtain a slurry;

[0010] The slurry is prepared into a film, and the film is attached to an LED device.

[0011] The inventors have tried to use octadecene as a reaction solvent, which has the advantages of low polarity and high boiling point, which is conducive to promoting the growth of quantum dots. However, it was found that when octadecene is used as a reaction solvent, the double bonds of octadecene are easily polymerized at high temperatures, which is not conducive to uniform quantum dot synthesis and reduces the quantum yield. Using dioctyl ether as a reaction solvent can avoid the double bond polymerization effect brought by octadecene, which is conducive to improving the quality of quantum dots.

[0012] The present invention utilizes the energy transfer principle of double perovskite and can adjust the luminescent color by changing the doping ratio of erbium ions.

[0013] In the preparation process, the erbium oleate precursor is synthesized first, which can reduce crystal defects and improve reaction efficiency.

[0014] In some embodiments, the molar ratio of cesium oleate, erbium oleate, indium acetate, bismuth acetate, silver acetate, benzoyl chloride, dioctyl ether, oleic acid, and oleylamine is 1.5-2.5:0.03-0.06:0.5-1:0.01-0.02:1:10-15:60-65:30-40:10-15;

[0015] The preferred ratio is 2.00:0.05:0.90:0.0125:1:13:62.95:31.54:10.99.

[0016] In some embodiments, the preparation method of the erbium oleate is: after mixing erbium acetate hydrate and oleic acid in proportion, heating in a nitrogen atmosphere to obtain erbium oleate.

[0017] Preferably, the heating temperature in a nitrogen atmosphere is 100-140° C., and the holding time is 15-25 min. More preferably, the heating temperature is 110-130° C., and the holding time is 20 min.

[0018] In some embodiments, the preparation method of cesium oleate is: cesium carbonate and oleic acid are mixed in proportion, and then heated under a nitrogen atmosphere to obtain cesium oleate.

[0019] Preferably, the heating temperature in a nitrogen atmosphere is 140-160° C., and the holding time is 15-25 min. More preferably, the heating temperature is 150° C., and the holding time is 20 min.

[0020] In some embodiments, cesium oleate, erbium oleate, indium acetate, bismuth acetate, silver acetate, benzoyl chloride, dioctyl ether, oleic acid and oleylamine are mixed in proportion, heated to 130-150° C. in a nitrogen atmosphere, and the reaction is stopped after reacting for 1-3 minutes.

[0021] Preferably, under a nitrogen atmosphere, the temperature is raised to 140° C. and the reaction is carried out for 2 minutes.

[0022] Preferably, the reaction is stopped by cooling with ice water to lower the temperature.

[0023] In some embodiments, in the mixed solution of cyclohexane and ethyl acetate, the volume ratio of cyclohexane to ethyl acetate is 2-5:1.

[0024] Preferably, in the mixed solution of cyclohexane and ethyl acetate, the volume ratio of cyclohexane to ethyl acetate is 2-4:1.

[0025] Further preferably, in the mixed solution of cyclohexane and ethyl acetate, the volume ratio of cyclohexane to ethyl acetate is 3: 1. The mixed solution of cyclohexane and ethyl acetate can enable the quantum dots to precipitate from the solvent with high polarity, which helps to obtain the precipitated quantum dots by centrifugation.

[0026] In some embodiments, the mass percentage of the inorganic polysilazane solution is 15-25 wt %, and the concentration of the quantum dot solution is 0.004-0.01 mmol / L.

[0027] Preferably, the volume ratio of the inorganic polysilazane solution to the quantum dot solution is 3-5:1. After mixing, ultrasonic treatment is performed for 2-5 minutes to separate excess oleylamine from the surface and allow the NH bonds of the inorganic polysilazane to fully react with the perovskite surface.

[0028] In some embodiments, the quantum dot solution is mixed with the inorganic polysilazane solution, dispersed by ultrasonication, and then the mixture is heated to 75-85° C. and stirred for reaction for 12-13 hours.

[0029] Preferably, the quantum dot solution and the inorganic polysilazane solution are mixed and dispersed by ultrasonication, and then the mixed solution is heated to 80° C. and stirred for reaction for 12-13 hours.

[0030] In some embodiments, the LED device is an LED micro-nano chip with an excitation wavelength of 385 nm.

[0031] In some embodiments, the method of preparing the slurry into a film is: drop the colloidal solution on a glass sheet, and use a scraper to evenly apply the film-forming solution to the substrate.

[0032] In some embodiments, the method of attaching the film to the LED device is: drop the colloidal solution on the LED microchip, and use a scraper to evenly spread the film-forming solution.

[0033] In a second aspect, the present invention provides a polarized LED device with adjustable emission color, which is prepared by the preparation method.

[0034] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0035] The present invention provides a method for preparing a polarized LED device with adjustable luminous color, which opens up new ideas for the development of adjustable LED color and linear polarization micro-nano light sources. 2 AgIn 0.98 Bi 0.02 Cl 6 And a series of quantum dots doped with bait ions of different concentrations are designed to transfer the original self-limited emission energy to the erbium ion energy level, so that the energy transfer efficiency can be changed by adjusting the bait ion doping concentration, and the luminescent color of the prepared LED optical device can be changed; at the same time, due to the self-limited state distortion, lattice asymmetry and self-assembly effect of the double perovskite, the quantum dots doped with bait ions have the characteristics of polarized luminescence, and the quantum dot solution can be mixed with the inorganic polysilazane solution, and the silicon oxide generation can be controlled and spin-coated into a film to prepare a highly stable and highly polarized micro-nano light source for use in the device, which can also be used as a polarized micro-nano light source for the development of optical devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0037] Figure 1 Cs described in Examples 1-4 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Transmission electron microscopy image of quantum dots.

[0038] Figure 2 Cs described in Examples 1-4 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Powder X-ray diffraction pattern of quantum dots.

[0039] Figure 3 Cs described in Examples 1-4 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Photoluminescence and absorption spectra of quantum dots.

[0040] Figure 4 Cs described in Examples 1-4 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Photoluminescence CIE spectrum of quantum dots.

[0041] Figure 5 Cs described in Examples 1-4 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Photoluminescence spectra of quantum dots at different angles.

[0042] Figure 6 Cs described in Examples 5-8 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 Normalized intensity spectra of quantum dots at different angles.

[0043] Figure 7 Cs described in Examples 9 and 10 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 LED photoluminescence spectra and CIE spectra of quantum dots at different angles. DETAILED DESCRIPTION

[0044] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0045] The present invention will be further described below in conjunction with the embodiments.

[0046] Embodiment 1:

[0047] (1) Preparation of precursor solution

[0048] 1623 mg of cesium carbonate and 20 ml of oleic acid were placed in a four-necked flask, and allowed to stand for 20 minutes under a nitrogen atmosphere. The magnetic stirring and heating device were turned on to raise the temperature to 120°C, and then kept warm for 30 minutes. After the reactants were completely dissolved, the temperature was raised to 150°C and kept warm for 20 minutes. After the solution obtained in the previous step was cooled to room temperature, stirring was stopped to obtain a cesium oleate precursor solution.

[0049] 720 mg of erbium (III) acetate hydrate and 10 ml of oleic acid were placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, and the magnetic stirring and heating device were turned on to raise the temperature to 120°C, followed by insulation for 30 min. After the reactants were completely dissolved, the temperature was raised to 150°C and maintained for 20 min to obtain an oleic acid bait precursor solution.

[0050] (2) Lead-free double perovskite Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Preparation of quantum dots

[0051] 1.0 ml of cesium oleate solution, 0.2 mmol of indium acetate, 0.0025 mmol of bismuth acetate, 0.2 mmol of silver acetate, 0.3 ml of benzoyl chloride, 5.0 ml of dioctyl ether, 2.0 ml of oleic acid, and 0.5 ml of oleylamine were placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, the magnetic stirring and heating device were turned on, and then the mixture was heated to 100 ° C and maintained at this temperature for 1 hour.

[0052] After the reactants were completely dissolved, the temperature was raised to 140°C, the reaction was stopped after 2 min, and the mixture was cooled with ice water.

[0053] Cyclohexane and ethyl acetate were added to the mixture in a volume ratio of 2:1, and the mixture was centrifuged at 8000 rpm for 8 minutes. The supernatant was discarded after precipitation. The addition of mixed reagents and centrifugation were repeated, and the supernatant was discarded to obtain quantum dots, which were dispersed in 10 ml of cyclohexane.

[0054] Embodiment 2:

[0055] Compared with Example 1, most of them are the same, except that in step 2), 1.0 ml of cesium oleate solution, 0.18 mmol of indium acetate, 0.0025 mmol of bismuth acetate, 0.2 mmol of silver acetate, 0.01 mmol of erbium oleate, 0.3 ml of benzoyl chloride, 5.0 ml of dioctyl ether, 2.0 ml of oleic acid, and 0.5 ml of oleylamine are placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, magnetic stirring and a heating device are turned on, and then the mixture is heated to 100° C. and maintained at this temperature for 1 hour.

[0056] Embodiment 3:

[0057] Compared with Example 1, most of them are the same, except that in step 2), 1.0 ml of cesium oleate solution, 0.18 mmol of indium acetate, 0.0025 mmol of bismuth acetate, 0.2 mmol of silver acetate, 0.05 mmol of erbium oleate, 0.3 ml of benzoyl chloride, 5.0 ml of dioctyl ether, 2.0 ml of oleic acid, and 0.5 ml of oleylamine are placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, the magnetic stirring and heating device are turned on, and then the mixture is heated to 100° C. and maintained at this temperature for 1 hour.

[0058] Embodiment 4:

[0059] Compared with Example 1, most of them are the same, except that in step 2), 1.0 ml of cesium oleate solution, 0.18 mmol of indium acetate, 0.0025 mmol of bismuth acetate, 0.2 mmol of silver acetate, 0.10 mmol of erbium oleate, 0.3 ml of benzoyl chloride, 5.0 ml of dioctyl ether, 2.0 ml of oleic acid, and 0.5 ml of oleylamine are placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, magnetic stirring and heating devices are turned on, and then the mixture is heated to 100° C. and maintained at this temperature for 1 hour.

[0060] Figure 1 Cs described in Examples 1-4 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 The transmission electron microscopy image of the quantum dots, after statistics and Gaussian fitting, showed that the size of the quantum dots was in the range of 12.74±0.08nm and had a high degree of crystallinity.

[0061] Figure 2 Cs described in Examples 1-4 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs2 AgIn 0.98 Bi 0.02 Cl 6 Powder X-ray diffraction diagram of quantum dots. When bait ions are doped into quantum dots, the crystal structure of the perovskite host is not changed, and the crystal structure of quantum dots is cubic. structure.

[0062] Figure 3 Cs described in Examples 1-4 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Photoluminescence spectrum and absorption spectrum of quantum dots. It can be clearly seen that Cs 2 Ag 6 In 0.98 Bi 0.02 Cl 6 The photoluminescence of the quantum dots showed a single broad emission band centered at 620 nm with a maximum half width (FWHM) of 179 nm. After erbium ion doping, the quantum dots showed broad STEs emission and four sharp emission peaks at 533, 559, 657, and 808 nm, corresponding to Er, 3+ The intrinsic 2 H 11 / 2 → 4 I 15 / 2 , 4 S 3 / 2 → 4 I 15 / 2 , 4 F 9 / 2 → 4 I 15 / 2 ,and 4 I 9 / 2 → 4 I 15 / 2 Transition.

[0063] Figure 4 Cs described in Examples 1-4 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 The photoluminescence CIE spectrum of quantum dots shows obvious changes in the CIE coordinates by changing the content of bait ion doping.

[0064] Figure 5 Cs described in Examples 1-4 of the present invention 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Photoluminescence spectra of quantum dots at different angles.

[0065] Embodiment 5:

[0066] Compared with Example 1, most of the steps are the same, except that in step 2), a mixed solution of cyclohexane and ethyl acetate in a volume ratio of 2:1 is added to the mixture, centrifuged at 8000 rpm for 8 minutes, and the supernatant is discarded after precipitation; the addition of mixed reagents and centrifugation are repeated, and the supernatant is discarded to obtain quantum dots, and the quantum dots are dispersed in 10 ml of cyclohexane. The solution is then diluted to 0.004 mmol / L, and the degree of polarization of the solution is 0.205.

[0067] Embodiment 6:

[0068] Compared with Example 1, most of the steps are the same, except that in step 2), a mixed solution of cyclohexane and ethyl acetate in a volume ratio of 2:1 is added to the mixture, centrifuged at 8000 rpm for 8 minutes, and the supernatant is discarded after precipitation; the addition of mixed reagents and centrifugation are repeated, and the supernatant is discarded to obtain quantum dots, and the quantum dots are dispersed in 10 ml of cyclohexane. The solution is then diluted to 0.003 mmol / L, and the degree of polarization of the solution is 0.214.

[0069] Embodiment 7:

[0070] Compared with Example 1, most of the steps are the same, except that in step 2), a mixed solution of cyclohexane and ethyl acetate in a volume ratio of 2:1 is added to the mixture, centrifuged at 8000 rpm for 8 minutes, and the supernatant is discarded after precipitation; the addition of mixed reagents and centrifugation are repeated, and the supernatant is discarded to obtain quantum dots, and the quantum dots are dispersed in 10 ml of cyclohexane. The solution is then diluted to 0.002 mmol / L, and the degree of polarization of the solution is 0.238.

[0071] Embodiment 8:

[0072] Compared with Example 1, most of the steps are the same, except that in step 2), a mixed solution of cyclohexane and ethyl acetate in a volume ratio of 2:1 is added to the mixture, centrifuged at 8000 rpm for 8 minutes, and the supernatant is discarded after precipitation; the addition of mixed reagents and centrifugation are repeated, and the supernatant is discarded to obtain quantum dots, and the quantum dots are dispersed in 10 ml of cyclohexane. The solution is then diluted to 0.001 mmol / L, and the degree of polarization of the solution is 0.240.

[0073] Figure 6 is Cs of Example 5-8 2 AgIn 0.98 Bi 0.02 Cl 6 The normalized intensity spectrum of quantum dots at different angles shows how the spatial arrangement and order of individual nanoparticles affect the degree of polarization.

[0074] Embodiment 9:

[0075] (1) Preparation of precursor solution

[0076] 1623 mg of cesium carbonate and 20 ml of oleic acid were placed in a four-necked flask, and allowed to stand for 20 minutes under a nitrogen atmosphere. The magnetic stirring and heating device were turned on to raise the temperature to 120°C, and then kept warm for 30 minutes. After the reactants were completely dissolved, the temperature was raised to 150°C and kept warm for 20 minutes. After the solution obtained in the previous step was cooled to room temperature, stirring was stopped to obtain a cesium oleate precursor solution.

[0077] 720 mg of erbium (III) acetate hydrate and 10 ml of oleic acid were placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, and the magnetic stirring and heating device were turned on to raise the temperature to 120°C, followed by insulation for 30 min. After the reactants were completely dissolved, the temperature was raised to 150°C and maintained for 20 min to obtain an oleic acid bait precursor solution.

[0078] (2) Lead-free double perovskite Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Preparation of quantum dots

[0079] 1.0 ml of cesium oleate solution, 0.2 mmol of indium acetate, 0.0025 mmol of bismuth acetate, 0.2 mmol of silver acetate, 0.3 ml of benzoyl chloride, 5.0 ml of dioctyl ether, 2.0 ml of oleic acid, and 0.5 ml of oleylamine were placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, the magnetic stirring and heating device were turned on, and then the mixture was heated to 100 ° C and maintained at this temperature for 1 hour.

[0080] After the reactants were completely dissolved, the temperature was raised to 140°C, the reaction was stopped after 2 min, and the mixture was cooled with ice water.

[0081] A mixed solution of cyclohexane and ethyl acetate in a volume ratio of 2:1 was added to the mixture, and the mixture was centrifuged at 8000 rpm for 8 minutes. The supernatant was discarded after precipitation. The addition of mixed reagents and centrifugation were repeated, and the supernatant was discarded to obtain quantum dots, which were dispersed in 10 ml of cyclohexane.

[0082] (3) Inorganic polysilazane can passivate double perovskite quantum dots

[0083] The quantum dot solution was mixed with a 20 wt % inorganic polysilazane solution, wherein the volume ratio of the quantum dot solution to the inorganic polysilazane solution was 1:4, and then the mixture was ultrasonicated for 3 minutes to obtain a quantum dot solution after passivation with the inorganic polysilazane.

[0084] (4) Make inorganic polysilazane achieve single-point approximate coating effect on double perovskite quantum dots

[0085] The mixed solution is heated and stirred, wherein the temperature is controlled at 80° C. and the time is controlled at 12 hours, so that the inorganic polysilazane is fully hydrolyzed to form a dense silicon oxide shell.

[0086] (5) Assemble the film with an LED chip, the emission wavelength of the LED chip is 390nm.

[0087] Embodiment 10:

[0088] (1) Preparation of precursor solution

[0089] 1623 mg of cesium carbonate and 20 ml of oleic acid were placed in a four-necked flask, and allowed to stand for 20 minutes under a nitrogen atmosphere. The magnetic stirring and heating device were turned on to raise the temperature to 120°C, and then kept warm for 30 minutes. After the reactants were completely dissolved, the temperature was raised to 150°C and kept warm for 20 minutes. After the solution obtained in the previous step was cooled to room temperature, stirring was stopped to obtain a cesium oleate precursor solution.

[0090] 720 mg of erbium (III) acetate hydrate and 10 ml of oleic acid were placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, and the magnetic stirring and heating device were turned on to raise the temperature to 120°C, followed by insulation for 30 min. After the reactants were completely dissolved, the temperature was raised to 150°C and maintained for 20 min to obtain an oleic acid bait precursor solution.

[0091] (2) Lead-free double perovskite Cs 2 AgIn 0.98 Bi 0.02 Cl 6 Preparation of quantum dots

[0092] 1.0 ml of cesium oleate solution, 0.18 mmol of indium acetate, 0.0025 mmol of bismuth acetate, 0.2 mmol of silver acetate, 0.10 mmol of erbium oleate, 0.3 ml of benzoyl chloride, 5.0 ml of dioctyl ether, 2.0 ml of oleic acid and 0.5 ml of oleylamine were placed in a four-necked flask, allowed to stand for 20 min under a nitrogen atmosphere, the magnetic stirring and heating device were turned on, and then the mixture was heated to 100 ° C and maintained at this temperature for 1 hour.

[0093] After the reactants were completely dissolved, the temperature was raised to 140°C, the reaction was stopped after 2 min, and the mixture was cooled with ice water.

[0094] A mixed solution of cyclohexane and ethyl acetate in a volume ratio of 2:1 was added to the mixture, and the mixture was centrifuged at 8000 rpm for 8 minutes. The supernatant was discarded after precipitation. The addition of mixed reagents and centrifugation were repeated, and the supernatant was discarded to obtain quantum dots, which were dispersed in 10 ml of cyclohexane.

[0095] (3) Inorganic polysilazane can passivate double perovskite quantum dots

[0096] The quantum dot solution was mixed with a 20 wt % inorganic polysilazane solution, wherein the volume ratio of the quantum dot solution to the inorganic polysilazane solution was 4:1, and then the mixture was ultrasonicated for 3 minutes to obtain a quantum dot solution after inorganic polysilazane passivation.

[0097] (4) Make inorganic polysilazane achieve single-point approximate coating effect on double perovskite quantum dots

[0098] The mixed solution is heated and stirred, wherein the temperature is controlled at 80° C. and the time is controlled at 12 hours, so that the inorganic polysilazane is fully hydrolyzed to form a dense silicon oxide shell.

[0099] (5) Assemble the film with an LED chip, the emission wavelength of the LED chip is 385 nm.

[0100] Figure 7 Cs described in Examples 9 and 10 2 AgIn 0.98 Bi 0.02 Cl 6 and Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 LED photoluminescence spectra and CIE spectra of quantum dots at different angles, Cs 2 AgIn 0.98 Bi 0.02 Cl 6 The prepared LED luminescence diagram is shown in Figure a. As the polarization angle increases, the luminescence peak gradually redshifts. After reaching 90°, when the polarization angle increases, the luminescence peak shifts to the blue. The CIE coordinates in Figure b also prove this experimental result. Er:Cs 2 AgIn 0.98 Bi 0.02 Cl 6 The prepared LED emission diagram is shown in Figure c. As the polarization angle increases, the emission peak gradually redshifts. After reaching 90°, when the polarization angle continues to increase, the emission peak appears to blueshift. The CIE coordinates in Figure d also prove this experimental result.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a polarized LED device with adjustable emission color, characterized in that: The steps include: Cesium oleate, erbium oleate, indium acetate, bismuth acetate, silver acetate, benzoyl chloride, dioctyl ether, oleic acid and oleylamine were mixed in proportion, heated to 120-170° C. in a nitrogen atmosphere, reacted for 1-5 minutes, and then the reaction was stopped; Adding a mixture of cyclohexane and ethyl acetate to the reaction solution, centrifuging, collecting the precipitate, repeating the operation to obtain quantum dots, dispersing the quantum dots in cyclohexane to obtain a quantum dot solution; The quantum dot solution and the inorganic polysilazane solution are mixed and dispersed by ultrasonication, and then the mixed solution is heated to 70-90° C. and stirred for reaction for 10-15 hours to hydrolyze the inorganic polysilane to form a dense silicon oxide shell to obtain a slurry; The slurry is prepared into a film, and the film is attached to an LED device.

2. The method for preparing a polarized LED device with adjustable emission color according to claim 1, characterized in that: The molar ratio of cesium oleate, erbium oleate, indium acetate, bismuth acetate, silver acetate, benzoyl chloride, dioctyl ether, oleic acid and oleylamine is 1.5-2.5:0.03-0.06:0.5-1:0.01-0.02:1:10-15:60-65:30-40:10-15.

3. The method for preparing a polarized LED device with adjustable emission color according to claim 1, characterized in that: The preparation method of erbium oleate is as follows: erbium acetate hydrate and oleic acid are mixed in proportion, and then heated in a nitrogen atmosphere to obtain erbium oleate; Preferably, the heating temperature in a nitrogen atmosphere is 100-140° C., and the insulation time is 15-25 min.

4. The method for preparing a polarized LED device with adjustable emission color according to claim 1, characterized in that: The preparation method of cesium oleate is as follows: cesium carbonate and oleic acid are mixed in proportion, and then heated under a nitrogen atmosphere to obtain cesium oleate; Preferably, the heating temperature in a nitrogen atmosphere is 140-160° C., and the insulation time is 15-25 min.

5. The method for preparing a polarized LED device with adjustable emission color according to claim 1, characterized in that: Cesium oleate, erbium oleate, indium acetate, bismuth acetate, silver acetate, benzoyl chloride, dioctyl ether, oleic acid and oleylamine were mixed in proportion, heated to 130-150° C. in a nitrogen atmosphere, and reacted for 1-3 minutes before stopping the reaction; Preferably, under a nitrogen atmosphere, the temperature is raised to 140° C. and the reaction is carried out for 2 min; Preferably, after stopping the reaction, ice water is used for cooling to lower the temperature to stop the reaction.

6. The method for preparing a polarized LED device with adjustable emission color according to claim 1, characterized in that: In the mixed solution of cyclohexane and ethyl acetate, the volume ratio of cyclohexane to ethyl acetate is 2-5:1; Preferably, in the mixed solution of cyclohexane and ethyl acetate, the volume ratio of cyclohexane to ethyl acetate is 2-4:1; Further preferably, in the mixed solution of cyclohexane and ethyl acetate, the volume ratio of cyclohexane to ethyl acetate is 3:

1.

7. The method for preparing a polarized LED device with adjustable emission color according to claim 1, characterized in that: The mass percentage of the inorganic polysilazane solution is 15-25wt%, and the concentration of the quantum dot solution is 0.004-0.01mmol / L; Preferably, the volume ratio of the inorganic polysilazane solution to the quantum dot solution is 3-5:1, and the mixture is ultrasonicated for 2-5 minutes after mixing.

8. The method for preparing a polarized LED device with adjustable emission color according to claim 1, characterized in that: The quantum dot solution and the inorganic polysilazane solution are mixed, ultrasonically dispersed, and then the mixed solution is heated to 75-85° C. and stirred for reaction for 12-13 hours; Preferably, the quantum dot solution and the inorganic polysilazane solution are mixed and dispersed by ultrasonication, and then the mixed solution is heated to 80° C. and stirred for reaction for 12-13 hours.

9. The method for preparing a polarized LED device with adjustable emission color according to claim 1, characterized in that: The LED device is an LED micro-nano chip with an excitation wavelength of 385nm; Preferably, the method of preparing the slurry into a film is: dropping the colloidal solution on a glass sheet, and using a scraper to evenly apply the film-forming solution onto the substrate; Preferably, the method of attaching the film to the LED device is: dropping the colloidal solution on the LED microchip, and using a scraper to evenly spread the film-forming solution.

10. A polarized LED device with adjustable emission color, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Red and green light perovskite quantum dot stable fluorescent powder based on SiO2 coating and preparation

    CN110872510A

  • Stable CsPbI3 perovskite quantum dot in polar solvent and preparation method thereof

    CN118027966A

  • Method for preparing antimony-doped cesium-indium-chloride lead-free perovskite nanocrystal through improved thermal injection method

    CN118270830A

  • Linear polarization low-threshold polarization laser light source capable of being treated by solution and preparation method of linear polarization low-threshold polarization laser light source

    CN119799332A

  • Preparation method for perovskite nanoparticles and optoelectronic device comprising the perovskite nanoparticles manufactured thereby

    KR102243623B1